2010
DOI: 10.1097/aln.0b013e3181dcd875
|View full text |Cite
|
Sign up to set email alerts
|

Fentanyl Does Not Reduce the Incidence of Laryngospasm in Children Anesthetized with Sevoflurane

Abstract: Two successive doses of 1.5 microg/kg fentanyl did not effectively prevent laryngospasm in children, aged 2-6 yr, anesthetized with sevoflurane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…More laryngospasm was observed with sodium thiopental. Erb et al (29) demonstrated that fentanyl was not able to reduce laryngospasm incidence in the children who were anesthetized with sevoflurane.…”
Section: Discussionmentioning
confidence: 99%
“…More laryngospasm was observed with sodium thiopental. Erb et al (29) demonstrated that fentanyl was not able to reduce laryngospasm incidence in the children who were anesthetized with sevoflurane.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the results should not be extrapolated when using other anaesthetic drugs such as propofol because laryngeal and respiratory reflex responses have been demonstrated to be different when propofol is administered compared with sevoflurane [10]. Third, no control group was included in this study; however, the stability of the model over a specific time frame has been previously examined in a separate group of children anaesthetised with sevoflurane and exposed to three repeated laryngeal stimulations [19] in a similar manner to those in the present study. The laryngeal and respiratory reflex responses were remarkably constant in successive stimulations and the results were in agreement with the work of Tagaito et al [11], who found no significant differences in the incidence of laryngeal and respiratory reflex responses that could be accredited to repeat stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing the incidence of these reflexes will potentially improve the safety of anaesthesia, and administration of lidocaine in this context has been advocated for many years, even though its exact impact remains unclear [13]. Although sevoflurane is widely used in children, not least because of its ability to obtund pharyngeal and laryngeal reflexes [28], laryngospasm occurs frequently [10,19] and adjuvant medication to reduce its incidence is warranted. The results of our study suggest that the incidence of laryngospasm is decreased after the intravenous administration of lidocaine; however, the timing of administration, for example, before extubation, must be carefully planned to obtain optimum effects because it is short-acting.…”
Section: Discussionmentioning
confidence: 99%
“…The role of opioids to prevent laryngospasm remains controversial [48,64]. However, remifentanyl is increasingly used to suppress laryngeal and bronchial reflex constriction during airway manipulations [65 • ].…”
Section: Anesthetic Agentsmentioning
confidence: 99%